RANCANG BANGUN SISTEM ANTRIAN PELAYANAN DI KECAMATAN SUKMAJAYA - Tri Tama Aditiya; Instianti Elyana; Hanafi Eko Darono - Universitas BSI; Tati Mardiana - Universitas Nusa Mandiri (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2022)
Abstract - Sukmajaya Subdistrict, Depok City in the queuing system for community services did not use any system at all, either conventional with manual serial numbers or serial numbers based on the system. So it is less effective and there is often a buildup when people want to get services in kecamtan. Therefore, Sukmajaya District needs a computerized queuing system that makes it easy for the community to avoid confusion in the service queue. In line with this system, it can also be used as a reference for monthly service reports in Sukmajaya District and service results recapitulation. The results of this study are to provide convenience in managing the queue, it is hoped that it will make it easier for ASNs and service employees in the futureKeyword : Planning System, Serial SystemAbstrak - Kecamatan Sukmajaya Kota Depok dalam sistem antrian untuk pelayanan masyarakat sama sekali tidak menggunakan sistem apapun, baik konvensional dengan nomer urut manual atau nomer urut berdasarkan sistem. Sehingga kurang efektif dan sering terjadi penumpukan pada saat masyarakat ingin mendapatkan pelayanan di kecamtan.Maka dari itu Kecamatan Sukmajaya membutuhkan suatu sistem antrian terkomputerisasi yang memudahkan masyarakat agar tidak terjadi kerancuan dalam antrian pelayanan. Sejalan dengan bila sistem ini, bisa juga sebagai acuan laporan pelayanan bulanan di Kecamatan Sukmajaya dan Rekapan hasil pelayanan Hasil dari penelitian ini adalah untuk memberikan kemudahan dalam mengelola antrian diharapkan akan memudahkan ASN dan Pegawai Pelayanan kedepanyaKata kunci: Perancangan Sistem, Sistem Antrian Pelayana